2021
DOI: 10.1016/j.chemosphere.2020.128628
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline antibiotics as precursors of dichloroacetamide and other disinfection byproducts during chlorination and chloramination

Abstract: Pollution of natural water and even source water with pharmaceuticals is problematic worldwide and raises concern about the possibility of disinfection byproduct (DBP) formation during subsequent water treatment. In this study, the formation of DBPs, especially dichloroacetamide (DCAcAm), was investigated during chlorination and chloramination of tetracyclines, which are a class of broad-spectrum antibiotics. DBPs including DCAcAm were formed during chlorination and chloramination of tetracycline (TC). Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 54 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Efraim et al [89] found that electrogenerated active chlorine had a better removal effect on antibiotics; the removal rate of ciprofloxacin and norfloxacin was close to 100%, and the removal rate of levofloxacin was about 75%. Although the chlorination method has a better removal effect on antibiotics, the byproducts generated by the chlorination method are often more toxic, which further limits the research and application of the chlorination method [90]. For example, He et al [91] found that the antibiotic fleroxacin forms halogenated disinfection byproducts during the chlorination degradation process, and the oxidative degradation products have higher biological toxicity.…”
Section: Strong Oxidant Oxidation Methodsmentioning
confidence: 99%
“…Similarly, Efraim et al [89] found that electrogenerated active chlorine had a better removal effect on antibiotics; the removal rate of ciprofloxacin and norfloxacin was close to 100%, and the removal rate of levofloxacin was about 75%. Although the chlorination method has a better removal effect on antibiotics, the byproducts generated by the chlorination method are often more toxic, which further limits the research and application of the chlorination method [90]. For example, He et al [91] found that the antibiotic fleroxacin forms halogenated disinfection byproducts during the chlorination degradation process, and the oxidative degradation products have higher biological toxicity.…”
Section: Strong Oxidant Oxidation Methodsmentioning
confidence: 99%
“…Previous studies have found that antibiotics can be transformed into N-DBPs by reacting with the disinfectant chloramine; for example, metronidazole could be oxidized by monochloramine disinfectant to form dicholoacetamide (DCAcAm) [ 32 ] and oxytetracycline could form the N-nitrosodimethylamine (NDMA) [ 33 ], which have been cited as research priorities by the U. S. EPA owing to their greater cytotoxicity and genotoxicity than currently regulated C-DBPs (e.g., THMs) [ 34 ]. The intricacies of DBP formation during disinfection are challenging to elucidate due to the influence of various factors such as pH values [ 35 ], disinfectant concentration, and inorganic ions [ 36 , 37 , 38 ]. Previous studies have highlighted the pH-dependent yield of NDMA during chloramine disinfection, emphasizing the significant impact of pH on DBP formation [ 33 ].…”
Section: Introductionmentioning
confidence: 99%